Digitalisation Studies With Ground Photogrammetric Method at Smintheion/Gülpınar Archaeological Site - Kaplan, Davut; Yuran, Ahmet (Fırat University, 2023)
In Smintheion/Gülpınar, in northwestern Anatolia, many important archaeological structures have been unearthed more than 40 years fieldwork, and this archaeological site has made significant contributions to the archeological studies with its significant historical background. At the same time, Smintheion stands out as an important field of study for many scientists in different fields of archeology, as well as for experts in the fields of architecture, epigraphy and restoration. And has been achieved successful results as a result of the multidisipliner work of archeology and engineering sciences in recently, such as documenting the remains with modern techniques. Here, three-dimensional modeling and photogrammetric studies were carried out, primarily mapping and city plan creation, and data were collected for the digitization of the ruins. In this direction, methods suitable for the field were determined, many measurements were made with the help of modern devices, and the data obtained as a result of the measurements were processed in digital environment and a base was created for the archaeological studies that were or will be made in Smintheion/Gülpınar. Throughout this short study, these digitization studies at Smintheion will be discussed together with the applied methods and the results will be presented.

Kuzeybatı Anadolu’da yer alan Smintheion/Gülpınar ören yerinde 40 yılı aşkın bir süredir devam eden çalışmalar sonunda önemli arkeolojik yapılar ortaya çıkarılmış, ören yeri sahip olduğu potansiyeli ile ülkemiz arkeoloji çalışmalarına önemli katkılar sunmuştur. Arkeoloji biliminin değişik alanlarında uzmanlaşan çok sayıda bilim adamı ile birlikte, mimarlık, epigrafi ve restorasyon alanındaki uzmanlar için de önemli bir çalışma sahası olarak öne çıkan Smintheion’da geçtiğimiz yıl içerisinde arkeoloji bilimi ile mühendislik bilimlerinin ortak çalışması sonucu başarılı sonuçlar elde edilmiştir. Burada başta haritalama ve kent planı oluşturulması olmak üzere, üç boyutlu modellemeler ve fotogrametrik çalışmalar yapılmış, ören yerinin sayısallaştırılması amacıyla veriler toplanmıştır. Bu doğrultuda araziye uygun yöntemler belirlenerek, modern cihazlar yardımıyla bir çok ölçüm yapılmış, yapılan ölçümler sonucunda elde edilen veriler dijital ortamda işlenerek Smintheion/Gülpınar’da yapılmış olan ya da yapılacak olan arkeolojik çalışmalar için altlık oluşturulmuştur. Bu kısa çalışma boyunca Smintheion’da yapılan bu sayısallaştırma çalışmaları uygulanan yöntemlerle birlikte ele alınacak ve elde edilen sonuçlar aktarılacaktır.
SMINTHEION/GÜLPINAR ÖREN YERİ YERSEL FOTOGRAMETRİK YÖNTEMLERLE SAYISALLAŞTIRMA ÇALIŞMALARI